Examining factors influencing Malaysian consumer purchase intention in halal cosmetic products: A conceptual framework / Munirah Khamarudin and Waida Irani Mohd Fauzi - Khamarudin, Munirah; Mohd Fauzi, Waida Irani (Universiti Teknologi MARA, Kedah, 2019)
Today, the issue of halal not only revolves in the food industry. Muslims also considering the halal notion even when they intent to purchase even cosmetic products. In response to this, the main objective of this study is to investigate the consumer intention in purchasing halal cosmetic products. In attempting to achieve this, there are four factors which can influence the intention to purchase halal cosmetic products namely attitudes, subjective norms, perceived behavioral control and brand awareness. The hypotheses are developed based on the previous studies and finally, a conceptual model of the study is proposed. In so doing, this paper expect to contribute to achieving a better understanding of what are the most factors influencing consumers intention to purchase the halal cosmetic products